2013
DOI: 10.3390/molecules181214711
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Arylthiophene-2-Carbaldehydes via Suzuki-Miyaura Reactions and Their Biological Evaluation

Abstract: A series of various novel 4-arylthiophene-2-carbaldehyde compounds were synthesized in moderate to excellent yields via Suzuki-Miyaura cross-coupling with different arylboronic pinacol esters/acids. The synthesized products were screened for their antibacterial, haemolytic, antiurease, and nitric oxide (NO) scavenging capabilities and interestingly, almost all products turned out to have good activities. 3-(5-Formylthiophene-3-yl)-5-(trifloromethyl)benzonitrile (2d) revealed excellent antibacterial activity, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Ali and coworkers assessed the antiurease activity of diverse 5-aryl-thiophene-2-carbaldehydes [68] . The authors observed a trend in which electron-withdrawing groups were more active at inhibiting the enzyme than their electron-donating counterparts, highlighting the di-halogenated compound ( 44 – Series A; Scheme 16 ) as the most active of the series [68] .…”
Section: Organic Substances As Urease Inhibitorsmentioning
confidence: 99%
“…Ali and coworkers assessed the antiurease activity of diverse 5-aryl-thiophene-2-carbaldehydes [68] . The authors observed a trend in which electron-withdrawing groups were more active at inhibiting the enzyme than their electron-donating counterparts, highlighting the di-halogenated compound ( 44 – Series A; Scheme 16 ) as the most active of the series [68] .…”
Section: Organic Substances As Urease Inhibitorsmentioning
confidence: 99%
“…Thiophene moiety is found to be very potent in various biological activities [ 15 , 16 , 17 ]. Anti-urease and nitric oxide (NO) scavenging activity of a series of 2-amino-6-arylbenzothiazoles were examined by Gul et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-urease and nitric oxide (NO) scavenging activity of a series of 2-amino-6-arylbenzothiazoles were examined by Gul et al [ 11 ]. Various 4-arylthiophene-2-carbaldehydes showed moderate to excellent ability against antibacterial, anti-urease, hemolytic, and antioxidant activities [ 16 ]. We became interested in synthesizing unsymmetrical bis-aryl (Ar and Ar′) substituted thiophene by taking the advantage of difference of reactivity of chloro and bromo moiety on thiophene ring.…”
Section: Introductionmentioning
confidence: 99%
“…The Suzuki–Miyaura cross-coupling reaction, which produces biaryls has proven to be the most important building blocks in organic synthesis owing to their industrial applications. We have previously reported the synthesis of arylthiophenes by regioselective Suzuki cross-coupling reactions and they were potentially studied as pharmaceutical agents [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%